(untitled) (Stavební obzor - Civil Engineering Journal, 2019)
Taking Yingzigou Bridge of Dezhou-Dajiawa railway as the engineering background, the three-dimensional fluid-solid coupling models of pile group caps were established on the basis of five-stage field monitoring data of the settlement and groundwater level drop by using FLAC3D software. On the basis of the field monitoring data checking, the variation of axial force and skin friction of piles at different positions under the condition of water level drop was simulated. The results show that with the underground water level dropped, the axial force of pile along the shaft increased first and then decreased. The cross section of maximum axial force moved down constantly. In the same ground water levels drop, the distance between the maximum axial force and neutral point of each pile and the top of the pile was corner pile > side pile> near borehole center pile > center pile. The size of the pile axial force and negative skin friction resistance was corner pile > side pile> near borehole center pile > center pile. The upper part of the pile was subjected to negative skin friction resistance. The skin friction resistance of each pile along the shaft increased first and then decreased. The lower part of the pile was subjected to positive skin friction resistance. The skin friction resistance of each pile along the shaft increased. The location of the maximum negative friction resistance was about 10m distance from the top of the pile. The maximum negative friction resistance of corner pile was -36.5kPa. The distance of neutral point of center pile from the top was 35.2m. The neutral point of each pile was in accordance with the position of the maximum axial force of the pile. A reliable basis was provided for high-speed railway survey and design and the prevention and control of land subsidence along the railway.